Simultaneous Renal Oncocytoma and Lymphoma: Interest of Lymphadenectomy - Angela Orcurto; Benoît Lhermitte; Alain Sermier; Dominik Berthold (Case Reports in Urology)
Kidney lesions may be difficult to diagnose only by radiological exams, often requiring proof by tissue biopsy. Moreover, if enlarged regional lymph nodes are also present, the spectrum of differential diagnoses is even greater. The role of regional lymph node dissection in this setting is not clearly established. We show the case of a patient with a kidney mass associated with a conglomerate of para-aortic and iliac lymphadenopathies corresponding to an oncocytoma and a nodular lymphocyte predominant Hodgkin' lymphoma, respectively. Diagnosis of these two lesions was performed by morphology and immunohistochemistry. This case reflects how imaging can mislead to diagnosis and how histological confirmation helps decide treatment management.